The Effect of Pender’s Health Promotion Model-based Education on the Physical Activity among Pregnant Women - Mitra Sabuni; Masoumeh Kheirkhah; Mahnaz Seyedoshohadaee; Shima Haghani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Purpose: The positive effects of physical activity during pregnancy have been completely recognized. However, given the lack of required knowledge and information, most of the pregnant women are inactive, and providing an educational program is thus of high significance for pregnant mothers. Given the multifactorial nature of physical activity, being affected by personal, interpersonal, environmental, and social factors, Pender’s health promotion model has been applied for designing the required intervention. The present study was thus designed and conducted to investigate the effect of an educational intervention based on Pender’s health promotion model on the physical activity of pregnant women.Method: The present study is a quasi-experimental one with a control group conducted at four Comprehensive Health Service Centers (both urban and suburban) in Sanandaj in 2020. Applying a random-stratified sampling method, two centers were dedicated to the control group and two centers were dedicated for the intervention group. With a continuous sampling plan, based on the inclusion exclusion criteria, as many as 88 pregnant women referring to the health service centers were selected and entered into the present study in two groups of intervention and control (each group consists of 44 participants). The control group received the regular care and training and the intervention group was provided with an education program based on Pender’s Health Promotion Model in five sixty-to-ninetyminute sessions with different methods and materials includingbrainstorming, lectures, group discussions, questions and answers, showing movies, and providing educational booklets and brochures distributed among women.The data collection tools include demographic questionnaires and the Pregnancy Physical Activity Questionnair by Chasan-Taber et al. For investigating the effect of the intervention, the questionnaires were completed 6 weeks after the end of the intervention for both intervention and control groups. The data were analyzed by using SPSS-25 as well as Chi-squared test, Fisher’s Exact Test, independent T-test, and paired t-test.Findings: Before initiating the educational intervention, there was no significant difference between the groups in terms of demographic and physical activity scores.But after the educational intervention, there was a statistically significant difference in the mean of total physical activity between the intervention and control groups(P<0.001).Conclusion: The present study confirms the effectiveness of an educational intervention based on Pender’s Health Promotion Model on promoting the pregnant women’s physical activity. Given the findings of the present study, it is thus recommended to apply Pender’s Health Promotion Model as a framework for designing the educational intervention to promote the physical activity among women